Policy Study of Industrial Designated Areas Based on Regional Regulation Number 1 of 2021 concerning Revision of Regional Spatial Plans in Serdang Bedagai Regency - Iswandani Lingga; Abdiyanto; Cut Nuraini (Yayasan Multidimensi Kreatif, 2024)
The regulation of industrial designation areas in the Spatial regional Planning of Serdang Bedagai Regency, regulated by Regional Regulation Number 1 of 2021, is the main focus of this research, specifically in identifying space utilization and land changes after the regulation and analyzing the content of the regulation.The regulation of industrial areas in the Spatial regional Planning of Serdang Bedagai Regency, based on Regional Regulation Number 1 of 2021, regulates the space utilization and classification of industrial activities to support economic growth in Serdang Bedagai Regency. This research identifies challenges in policy implementation, such as space utilization that is not in accordance with the Spatial regional Planning, licensing obstacles, and coordination between agencies, which results in regulatory incompatibility and disrupts regional economic growth. Although regulations aim to support industrial development, program vagueness, weaknesses in supervision and an obstructed licensing process due to conflicting regulations will affect the development of industrial estates in Serdang Bedagai.